CryoEM reveals oligomeric isomers of a multienzyme complex and assembly mechanics - Jane K.J. Lee; Yun-Tao Liu; Jason J. Hu; Inna Aphasizheva; Ruslan Aphasizhev; Z. Hong Zhou (Journal of Structural Biology: X, 2023)
Propionyl-CoA carboxylase (PCC) is a multienzyme complex consisting of up to six α-subunits and six β-subunits. Belonging to a metabolic pathway converging on the citric acid cycle, it is present in most forms of life and irregularities in its assembly lead to serious illness in humans, known as propionic acidemia. Here, we report the cryogenic electron microscopy (cryoEM) structures and assembly of different oligomeric isomers of endogenous PCC from the parasitic protozoan Leishmania tarentolae (LtPCC). These structures and their statistical distribution reveal the mechanics of PCC assembly and disassembly at equilibrium. We show that, in solution, endogenous LtPCC β-subunits form stable homohexamers, to which different numbers of α-subunits attach. Sorting LtPCC particles into seven classes (i.e., oligomeric formulae α0β6, α1β6, α2β6, α3β6, α4β6, α5β6, α6β6) enables formulation of a model for PCC assembly. Our results suggest how multimerization regulates PCC enzymatic activity and showcase the utility of cryoEM in revealing the statistical mechanics of reaction pathways.